BoNT-A related changes of cortical activity in patients suffering from severe hand paralysis with arm spasticity following ischemic stroke - Veverka, Tomáš; Hluštík, Petr; Tomášová, Zuzana; Hok, Pavel; Otruba, Pavel; Král, Michal; Tüdös, Zbyněk; Zapletalová, Jana; Herzig, Roman; Krobot, Alois; Kaňovský, Petr (Journal of the neurological sciences, 2012)
BACKGROUND: Investigations were performed to localize and analyze the botulinum toxin (BoNT-A) related changes of cerebral cortex activation in chronic stroke patients suffering from severe hand paralysis with arm spasticity. Effects on task- related cerebral activation were evaluated by functional magnetic resonance imaging (fMRI). METHODS: 14 patients (5 males, 9 females, mean age 55.3 years) suffering from upper limb post-stroke spasticity were investigated. The change of arm spasticity was assessed by using the modified Ashworth scale (MAS). FMRI sessions were performed before (W0), four weeks (W4) and 11 weeks (W11) after BoNT-A application. Patients were scanned while performing imaginary movement with the impaired hand. Group fMRI analysis included patient age as a covariate. RESULTS: BoNT-A treatment was effective in alleviation of arm spasticity. Mean MAS was at Week 0: 2.5 (SD 0.53), at Week 4: 1.45 (SD 0.38), at Week 11: 2.32 (SD 0.44). Task-related fMRI prior to the treatment showed extensive activation of bilateral frontoparietal sensorimotor cortical areas, anterior cingulate gyrus, pallidum, thalamus and cerebellum. Effective BoNT-A treatment (W4) resulted in partial reduction of active network volume in most of the observed areas, whereas BoNT-free data (W11) revealed further volume reduction in the sensorimotor network. On direct comparison, significant activation decreases associated with BoNT-A treatment were located in areas outside the classical sensorimotor system, namely, ipsilesional lateral occipital cortex, supramarginal gyrus and precuneus cortex. On comparison of W4 and W11, no activation increases were found, instead, activation further decreased in ipsilesional insular cortex, contralesional superior frontal gyrus and bilateral frontal pole. CONCLUSIONS: Whole brain activation patterns during BoNT-A treatment of post-stroke arm spasticity and further follow up document predominantly gradual changes both within and outside the classical sensorimotor system.
Keywords: dospělí; cévní mozková příhoda; Magnetic Resonance Imaging; Humans; lidé středního věku; Middle Aged; magnetická rezonanční tomografie; Cerebral Cortex; Brain Ischemia; mužské pohlaví; mapování mozku; Stroke; Psychomotor Performance; paže; nervosvalové látky; Adult; Botulinum Toxins, Type A; botulotoxiny typu A; mozková kůra; Arm; ischemie mozku; svalová spasticita; ženské pohlaví; Brain Mapping; lidé; Paralysis; paralýza; Aged; Muscle Spasticity; Neuromuscular Agents; senioři; Male; psychomotorický výkon; Female